A Study on influence of organic ligands on migration of heavy metals through compacted clayey soil - Yantrapalli, Sudheer Kumar; P, Hari Krishna; K, Srinivas (UIR PRESS, 2018)
This paper presents the feasibility study on utilization of locally available clayey soil as Compacted Clay Liner based on its contaminant migration capacity under the presence of organic chemical EDTA (Ethylene Diamine Tetra acetic Acid) which is abundantly released into the environment. Lead, Nickel, cadmium and chromium ions was selected as contaminants and its migration properties are assessed by conducting column studies with a single and multiple heavy metal solution with the EDTA. From the experimental investigations, it is revealed that with the presence of EDTA, the contaminant breakthrough time get reduced due to soluble metal – EDTA complex formation. At pH 2, interaction with multi metal, the mobility was increased and the order of mobility was observed as Cr > Cd > Ni > Pb. With the presence of EDTA in multi metal system at pH 2, the order of the mobility was Cr > Ni > Cd > Pb and at pH 7 the mobility of heavy metals were increased the order was Cr > NI > Pb > Cd. This study reveals that locally available clayey soil is capable of retaining heavy metals and it may be used as a compacted clay liner, where organic chemical like (EDTA) ingression is present.